(untitled) (Clinics, 2013)
OBJECTIVE: To investigate parental smoking patterns and their association with wheezing in children. METHODS: We performed a case-control study that included 105 children between 6 and 23 months of age who were divided into two groups: cases (children with 3 previous episodes of wheezing) and controls (healthy children without wheezing). The children's exposure to cigarette smoking was estimated using a questionnaire completed by the mothers and by the children's urinary cotinine levels. RESULTS: Based on both the questionnaire results and cotinine levels, exposure to cigarette smoking was higher in the households of cases in which the incidence of maternal smoking was significantly higher than that of paternal smoking. Children in this group were more affected by maternal smoking and by the total number of cigarettes smoked inside the house. Additionally, the questionnaire results indicated that the risk of wheezing was dose dependent. The presence of allergic components, such as atopic dermatitis and siblings with allergic rhinitis and asthma, greatly increased the odds ratio when wheezing was associated with cotinine levels. CONCLUSION: Children exposed to tobacco smoke have an increased risk of developing wheezing syndrome. This risk increases in association with the number of cigarettes smoked inside the house and the presence of other allergic components in the family.